Education and work-related mental health: Higher educated employees are worse off - Anna Katharina Pikos (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
This paper analyzes the relationship between work-related mental health and education in the German working population using cross sectional survey data from 2006 and 2012. Low education is associated with lower mild health problems, higher education with increased mild and medium severe problems. In the Job Demands and Resources model, work-related mental health problems arise from an imbalance between job demands and resources. Low education is significantly associated with lower job demands and resources but not with a different stress perception of missing resources. Higher educated have significantly higher demands and resources and perceive high job demands as more stressful. Education is also associated with less job satisfaction but there is suggestive evidence for monetary and some non-monetary compensation.
Keywords: I10; I26; J28; 330; work-related mental health; returns to education; job satisfaction